Gamification as a Strategy to Improve Speaking Skill in English as a Foreing Language - Yumisaca Valente, Cintya Maribel (2025)
The present research aimed to analyze the influence of gamification on the speaking skill improvement of students of 9th year of basic education “B” at Unidad Educativa Simon Rodriguez, high school during the academic year 2024-2025. This quasi-experimental research had a population formed by thirty-six participants who were distributed into the control group and the experimental group. Both groups took were diagnosed through the Flyers A2 test speaking part from Cambridge Assessment webpage. The pre-test revealed a low level of speaking skill performance. Afterwards, students from the experimental group participated in English classes with a main focus on the application of gamification activities. After this intervention, students were given the post-test which revealed that they have improved. Therefore, it is concluded that the application of gamification positively influenced on the speaking skill improvement of participants. For this reason, it is highly recommended that English teachers apply gamification not only with ninth graders but also with the rest of the levels to contribute with the teaching-learning process.